Addressing the Psychosocial Needs of Individuals with Communication Disorders: The Integration of Animal-Assisted Therapy within Counseling - Atherton, W. Leigh; Hudock, Daniel (Seminars in Speech and Language, 2022)
Individuals with speech, language, and communication disorders often present with psychosocial concerns that span the physiological, intrapersonal, and interpersonal domains of functioning. Despite this fact, the provision of counseling service by speech-language pathologist (SLP) that directly addresses clients' psychosocial needs is sparse. Research shows the primary counseling strategy used by therapists is psychoeducation, failing to effectively address the psychosocial concerns. Integrating complementary approaches to traditional counseling in SLP can enhance both the quality of therapeutic intervention and client outcomes. The purpose of this article is to demonstrate the potential of animal-assisted therapy (AAT) as an adjunctive or complementary approach for counseling within SLP. A review of literature demonstrates a need for improved counseling service provision within SLP treatment, as well as the benefits of integrating AAT. A framework for how AAT intentions and techniques fit within SLP Scope of Practice counseling activities is presented, along with case examples to demonstrate how AAT can be integrated within SLP treatment. It is concluded that the integration of AAT as a complementary approach to traditional SLP counseling can enhance both the frequency of counseling services provided and clients' psychosocial outcomes.
Keywords: psychosocial functioning; animal-assisted therapy; counseling